Electric Circuits - Nilsson, James William; Riedel, Susan A.; Shattuck, David P.; Wittels, Norman (Reading, Mass. : Addison-Wesley Pub. Co., 1993)
-- Introduction to Pspice (3C.) -- Solution manual 2V ( V.1 ch.1-10; V.2 ch. 11-20.) -- Instructor's road map
2. Introduction to PSpice: a supplement
Includes index.
Keywords: Electric circuits